2016
DOI: 10.1016/j.neurobiolaging.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral sphingolipids are associated with variation in white matter microstructure in older adults

Abstract: Sphingolipids serve important structural and functional roles in cellular membranes and myelin sheaths. Plasma sphingolipids have been shown to predict cognitive decline and Alzheimer’s disease (AD). However, the association between plasma sphingolipid levels and brain white matter (WM) microstructure has not been examined. We investigated whether plasma sphingolipids (ceramides, sphingomyelins) were associated with MRI-based diffusion measures, fractional anisotropy (FA) and mean diffusivity (MD), 10.5 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…Mielke et al (2010a) reported that elevated SM and Cer(d18:1) are early predictors of memory impairment in a longitudinal study. Another study revealed that higher plasma Cer(d18:1) were associated with poorer cerebral white matter microstructure (Gonzalez et al 2016). These studies suggest that plasma sphingolipids may have a biological role in the pathogenesis in neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Mielke et al (2010a) reported that elevated SM and Cer(d18:1) are early predictors of memory impairment in a longitudinal study. Another study revealed that higher plasma Cer(d18:1) were associated with poorer cerebral white matter microstructure (Gonzalez et al 2016). These studies suggest that plasma sphingolipids may have a biological role in the pathogenesis in neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, increases in plasma ceramides have been shown to predict cognitive decline and hippocampal volume loss in patients with mild cognitive impairment (Mielke et al 2010b). Furthermore, elevated circulating ceramides were associated with a worsening of white matter microstructure in cognitively normal patients (Gonzalez et al 2016). These studies highlight the importance of sphingolipid metabolism for central nervous system function and the potential for peripheral ceramides to influence the brain.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…; Gonzalez et al . ). Although elevated ceramide was not observed in our study, an approximately fivefold increase in its phosphorylated form, Cer‐1‐phosphate, was seen in the HD myelin layer.…”
Section: Discussionmentioning
confidence: 97%